Special Purpose Vehicles (SPV): a manifestation of Islamic Financial Innovation - Oseni, Umar Aimhanosi (ISRA & Thomson Reuters, 2015)
This paper examines the legality or otherwise of SPVs in Islamic law and considers the use of such structures in sukuk issuance as a manifestation of Islamic financial innovation.